The Effect of Human Resource Management Practices on Turnover Intention of Manufacturing Employees in Indonesia; the Mediation Role of Career Satisfaction - Armina, Sesaria Nur; Etikariena, Arum (Budapest International Research and Critics University, 2022)
This study aims to ensure that human resource management practices are believed to be one of the solutions to reduce employee turnover intentions. However, not all studies show that human resource management practices can provide significant results in reducing exit intentions. This research is research with a quantitative approach and is research with correlation analysis test using SPSS version 26.0 and a mediation analysis test using PROCESS MACRO version 4.0 which was developed by Andrew Hayes. Sampling in this study used non-probability sampling with the type of convenience sampling. The characteristics in this study are employees who work in the manufacturing industry with a minimum position of staff, and a minimum service period of one year. Based on the results of the hypothesis analysis test, it is known that before the mediator variable was added to the relationship between HRMP and intention to leave, it was found that the practice of human resource management (HRMP) had a negative relationship with the intention to leave in manufacturing employees in Indonesia with the result (b = -0.23 t = - - 7.41; p = 0.00). In addition, the practice of human resource management (HRMP) was also found to have a positive relationship with employee career satisfaction. Then, career satisfaction was found to have a negative relationship with employees' leaving intentions, but this study also found that career satisfaction did not mediate the relationship between human resource management practices (HRMP) and exit intentions among manufacturing employees in Indonesia.